Forced Marriage as a Form of Sexual Violence Against Child Victims of Rape from a Human Rights Perspective - Syabilal Ali; Slamet Tri Wahyudi; Handoyo Prasetyo; Handar Subhandi Bakhtiar; Irwan Triadi (International Journal of Sociology and Law, 2025)
Forced marriage of child victims of rape is a phenomenon that places children in a position of double victimization, both as victims of sexual crimes and as subjects who lose their human rights to determine their future freely and with dignity. This research aims to examine forced marriage in the framework of sexual violence against children from the perspective of criminal law and human rights. In its approach, this research uses a normative juridical method with a statutory approach, conceptual approach, comparative approach, and case approach. The results show that forced marriage not only violates children's rights to protection from sexual violence as stipulated in Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, but also violates the principles of non-discrimination, the best interests of the child, and the right to physical and psychological integrity as guaranteed in the Convention on the Rights of the Child (CRC) and other international human rights instruments. This research emphasizes the importance of legal recognition of forced marriage as a form of sexual violence and the need for a comprehensive policy in the handling and recovery of child victims.